A dinâmica urbana das regiões metropolitanas brasileiras - Mauro Borges Lemos; Sueli Moro; EIenice Biazi; Marco Crocco (Economia Aplicada, 2003)
This article aims to analyse the comparative performance of the metropolitan areas in Brazil. Its focus is on the urban agglomeration and disagglomeration factors underling their performance. Initially, we presentthe theoretical and methodological background of our motivation for further definition ofthe relevant variable for the analysis. The next step shows the stylised facts of the recent development of these metropolitan areas. In the third section we present the database and the techniques of multivariate analysis that will be used to analysed the coefficients created as proxies of the variables from the urban rent model developed in the first section. In the fourth section we estimate the basic agglomeration and disagglomeration factors based on PNADs database and the results show some important features regarding the comparative advantages and bottlenecks of these urban areas. The concluding remarks highlight some public policies directed to enhance their attraction capacity of new activities and to overcome economic and social dualism in these Brazilian metropolitan areas.